Community Empowerment Model through Café Sawah to Enhance Income-Generating Activities in Pujon Kidul, Indonesia - Edi Widianto; Mustofa Kamil; Joni Rahmat Pramudia (MASI Mandiri Edukasi, 2026)
Prior to the establishment of Café Sawah, Pujon Kidul Village relied primarily on agriculture and faced unemployment, limited economic diversification, and relatively low educational attainment. This study aims to analyse how Café Sawah functions as a community empowerment model that enhances income-generating activities in Pujon Kidul Village, Indonesia. A qualitative approach was employed, using semi-structured interviews with 11 informants: a community leader, village officials, a BUMDes Sumber Sejahtera manager, youth organisation representatives, and Café Sawah managers. Data were collected through interviews, observations, and document analysis, and analysed through data reduction, data display, conclusion drawing, and thematic interpretation; triangulation and member checking were used to strengthen credibility. The findings show that Café Sawah developed through collaborative governance involving the village government, BUMDes, local communities, and external stakeholders. The empowerment process combined community participation, utilisation of local resources, institutional coordination, and capacity building, thereby expanding locally accessible employment and business opportunities beyond agriculture. Tourism development reportedly created employment opportunities for approximately 200 individuals, involved workers from poor households, strengthened MSME participation and local product markets, contributed IDR 162.5 million annually to the village’s own-source revenue, and supported BUMDes-managed business activities generating approximately IDR 1.7 billion per year. These findings indicate broader access to productive activities and local economic opportunities rather than uniform income growth across all households. This study contributes an empirically grounded model showing how community-based tourism coordinated through BUMDes can connect participatory empowerment, village institutions, and local resource utilisation with diversified income-generating activities.